Analisis Efektivitas dan Penyebab Keterlambatan Pembayaran Berdasarkan SOP Pembayaran di PT. XYZ - Indri Yulia Rahmah; Dimas Nugroho Dwi Seputro (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
One operational problem that can impact cash flow, supply chain continuity, and company relationships is supplier payment delays. The Standard Operating Procedures (SOP), which specify a maximum payment duration of 30 days after invoice receipt, have not been fully followed with by supplier payment practices, according to internal data at PT. XYZ. The purpose of this study is to evaluate the efficiency of supplier payments and pinpoint the causes of PT. XYZ's payment delays. Using supplier payment transaction data from the last three months, including invoice receipt dates, due dates, and actual payment dates, a descriptive quantitative approach was used. Company records and interviews with procurement and finance staff assisted in the data collection process. The findings show that, on average, payments are completed between 45 and 50 days following invoice receipt, which causes delays of roughly 15 to 20 days after the SOP deadline. Inadequate documentation, poor internal communication, erratic cash flow, and a manual invoice verification procedure are the main causes of these delays. The results indicate that PT. XYZ's supplier payment processes have not yet been successfully implemented and need methodical enhancements to increase payment timeliness.